Incidence and Predictors of Acute Symptomatic Seizures After Stroke at A Tertiary Care Hospital: Incidence and Predictors of Acute Symptomatic Seizures - Gohar Ali, Syed; Hyder, Fezan; Kumari, Monika; Jazil Faruqi, Sidra; Abbasi, Irfana; Naeem Shahbaz, Naila (Pakistan Journal of Health Sciences, 2023)
Neurological deterioration can occur in approximately 15% of patients with acute stroke. Several mechanisms can lead to ischemic lesion extension and subsequent neurological worsening, including re-occlusion, edema progression, and cardiovascular instability. Stroke is one of the main causes of morbidity and mortality worldwide. Objective: To determine the Incidence and predictors of acute symptomatic seizures after stroke at a tertiary care hospital. Methods: This Descriptive Cross-Sectional Study was conducted at Department of Neurology, Civil Hospital, Karachi, Pakistan, from April 19, 2019 to October 18, 2019. Informed consent from all the patients who fulfilled the inclusion criteria was taken after explaining the procedure, risks and benefits of the study. CT scan & continuous twelve-lead ECG were performed. Assessment for associated factors of ischemic stroke i.e., seizure, atrial fibrillation and family history of stroke were noted. All the collected data were entered into the proforma attached at the end and used electronically for research purpose. Results: Mean ± SD of age was found to be 63.14±16.7 years. Out of 251 patients, 137 (54.6%) patients were male and 114 (45.4%) were female. Diabetes Mellitus was noted in 97 (38.6%) patients. Factors associated with acute ischemic stroke i.e., seizure was noted in 31 (12.1%) while atrial fibrillation was noted in 68 (27.1%) patients and positive family history of stroke was documented in 46 (18.3%). Conclusions: It is to be concluded that atrial fibrillation was found to be the major modifiable associated factors in the development of stroke. Controlling of these risk factors might reduce the risk of stroke.